A type system for object models. - Edwards, Jonathan (Software engineering notes.)
A type system for object models is described that supports subtyping, unions, and overloading of relation names. No special features need be added to the modelling language; in particular, there are no casts, and the meaning of an object model can be understood without mentioning types. A type error is associated with an expression that can be proved to be _irrelevant_, in the sense that it can be replaced by an empty set or relation without affecting the value of its enclosing constraint. Relevance is computed by a simple abstract interpretation.